The Day After Report of a Survey of Effects of Viewing and Beliefs about Nuclear War - Cross, Theodore P.; Saxe, Leonard ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The psychological effects on viewers of the television film "The Day After," designed to dramatize the possibility of nuclear war and its horrible consequences, were examined by this study. Subjects were 435 residents of the Boston metropolitan area who were randomly sampled from area telephone directories and interviewed by telephone. It appears that "The Day After" accomplished its implicit goals in terms of its effects on viewers' awareness and emotions. Results showed that the film raised viewers' estimate of the likelihood of nuclear war and lowered their estimate of the likelihood of surviving one, stimulated them to think more about the issue of nuclear war, and moved them to be more upset about nuclear war after watching the film. Psychologists need to research with more extensive designs the effect of television films both on viewers' beliefs and reactions and on their actions on issues. (RM)
ERIC Note: Paper presented at the Annual Meeting of the American Psychological Association (92nd, Toronto, Ontario, Canada, August 24-28, 1984). For related papers, see SO 016 399-400.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audience Analysis; Majority Attitudes; Mass Media Effects; Nuclear Warfare; Psychological Studies; Psychology; Public Opinion; Research Needs; Social Attitudes; Television Research; Day After (The); Reports, Research; Speeches/Meeting Papers